The RNA binding protein SRSF1 is a master switch of gene expression and regulation in the immune system. (February 2021) - Paz, Sean; Ritchie, Anastasia; Mauer, Christopher; Caputi, Massimo
Highlights: SRSF1 regulates the transcription of CD3ζ and IL-2. SRSF1 is downregulation in SLE patients. SRSF1 affects the splicing of cytokines and transmembrane signal-transducing receptor. SRSF1 regulates the stability and nuclear export of mRNAs coding for cytokines. SRSF1 modulates miRNA processing. Abstract: Serine/Arginine splicing factor 1 (SRSF1) is an RNA binding protein abundantly expressed in most tissues. The pleiotropic functions of SRSF1 exert multiple roles in gene expression by regulating major steps in transcription, processing, export through the nuclear pores and translation of nascent RNA transcripts. The aim of this review is to highlight recent findings in the functions of this protein and to describe its role in immune system development, functions and regulation.